The spatiotemporal patterns and network characteristics of emissions embodied in the international trade of livestock products - Wang, Xiang; Qiang, Wenli; Liu, Xiaojie; Yan, Simin; Qi, Yumei; Jia, Zhuo; Liu, Gang (Journal of environmental management, 2022)
Livestock production is greenhouse gas (GHG) emission intensive, and thus the increasing international trade of livestock products in recent decades has resulted in increased embodied emissions. Considering the varying emission intensity in production in different countries and the expected further increase in livestock product trade in the future, it becomes crucial to understand the spatial and temporal dynamics of such embodied GHG emissions for climate change mitigation in the livestock sector. In this study, we aimed to address such gaps and analyzed the spatiotemporal patterns and network characteristics of GHG emissions embodied in the international trade of seven major categories of livestock products among 228 world economies during 1986–2017.